2022
DOI: 10.1093/rb/rbac099
|View full text |Cite
|
Sign up to set email alerts
|

Inhalable microparticles as drug delivery systems to the lungs in a dry powder formulations

Abstract: Inhalation-administrated drugs remain an interesting possibility of addressing pulmonary diseases. Direct drug delivery to the lungs allows one to obtain high concentration in the site of action with limited systemic distribution, leading to a more effective therapy with reduced required doses and side effects. On the other hand, there are several difficulties in obtaining a formulation that would meet all the criteria related to physicochemical, aerodynamic, and biological properties, which is the reason why … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 163 publications
(219 reference statements)
0
4
0
Order By: Relevance
“…NGI measurements offer strong indications for the clinical performance of a formulation, exhibiting a notable correlation with in vivo results. [ 70 ] The MMAD values of 6.7 and 7.2 μm determined here for the PLGA/lysine and PLGA–PDA/lysine h‐μPs, respectively, are slightly larger than the optimal range for alveolar deposition; accordingly, these h‐μPs are likely to impact in the central airways such as the bronchi and bronchioles. The GSD calculations indicate a favorable particle size distribution: the FPF is characterized as the proportion of particles possessing an aerodynamic diameter of <5 μm, whereas the FPD denotes the absolute mass of particles from the FPF across all stages of the NGI.…”
Section: Resultsmentioning
confidence: 79%
“…NGI measurements offer strong indications for the clinical performance of a formulation, exhibiting a notable correlation with in vivo results. [ 70 ] The MMAD values of 6.7 and 7.2 μm determined here for the PLGA/lysine and PLGA–PDA/lysine h‐μPs, respectively, are slightly larger than the optimal range for alveolar deposition; accordingly, these h‐μPs are likely to impact in the central airways such as the bronchi and bronchioles. The GSD calculations indicate a favorable particle size distribution: the FPF is characterized as the proportion of particles possessing an aerodynamic diameter of <5 μm, whereas the FPD denotes the absolute mass of particles from the FPF across all stages of the NGI.…”
Section: Resultsmentioning
confidence: 79%
“…Several strategies that aimed to improve the targeting and effectiveness of drugs inhaled from DPIs were proposed using the functionalization of the surface of drug particles, which helps to increase both aerosolization and bioavailability. A recent overview by Knap et al [ 113 ] indicated various approaches of formulating solid inhalable drug microparticles using polysaccharides (e.g., chitosan and hyaluronic acid), lipids (for instance, PS phospholipids such as dipalmitoyl phosphatidylcholine, DPPC, or dipalmitoyl phosphatidylglycerol, DPPG), proteins (e.g., fibroin), or polymers (such as poly(lactide-co-glycolide), PLGA, or polycaprolactone, PCL). The obtained effect on their bioavailability can include tuning the residence time on the lung surface and/or the rate of uptake by alveolar macrophages (AMs).…”
Section: Selected Concepts and Methods Of Improvement Of Targeted Aer...mentioning
confidence: 99%
“…Several strategies that aimed to improve the targeting and effectiveness of drugs inhaled from DPIs were proposed using the functionalization of the surface of drug particles, which helps to increase both aerosolization and bioavailability. A recent overview by Knap et al [113] indicated various approaches of formulating solid inhalable drug microparticles using polysaccharides (e.g., chitosan and hyaluronic acid), lipids (for instance, PS phospholipids such as dipalmitoyl phosphatidylcholine, DPPC, or dipalmitoyl phosphatidylglycerol, DPPG), proteins (e.g., fibroin), or polymers (such as poly(lactide-coglycolide), PLGA, or polycaprolactone, PCL). The obtained effect on their bioavailability can include tuning the residence time on the lung surface and/or the rate of uptake by alveolar macrophages (AMs).…”
Section: Targeted Drug Delivery By Functionalized Particles and Non-c...mentioning
confidence: 99%